We could be so good together: A Presentation of the Multinational Enterprises’ International Joint Venture Strategy Effectiveness - M. Ikhwan Maulana Haeruddin; Analtha Farhansyah; Muhammad Ilham Haeruddin; Muhammad Alfi Rifadli Mansur (Har Press Indonesia, 2020)
The main purpose of this paper is to discuss and talking about International Joint Ventures (IJVs) and the factors of Multinational Enterprises (MNEs) using IJVs strategy for entering the global market, and also elaborate what are the advantages and disadvantages of using IJVs as a strategy and provide the reader with example of successful and unsuccessful IJVs. This paper also provides the reader understanding about IJVs how Telkom Indonesia could be success with Telstra and How could be TLC Company fail partnership with Alcatel Company. Furthermore, what drive them to be successful and unsuccessful are based on the analysis of two examples case study.